Religious Tolerance in France: A Perspective of Maqasid Shari'a - Lalu Supriadi Bin Mujib; Khairul Hamim (Khazanah Sosial, 2022)
This study examines religious tolerance in France from the perspective of Maqasid Shari'a. This study employed a qualitative approach with a case study design. The study was conducted in 2019, taking place in France. Data collection techniques were carried out using observation, in-depth interviews, and documentation also the informants were selected by purposive sampling and snowball sampling. Data analysis used the critical analysis method through in-depth interviews with religious leaders, organizational leaders associated with inter-religious harmony organizations, community leaders, and youth leaders. This study revealed France's position as a country which ready to accept religious pluralism and guarantees constitutional, historical and factual tolerance among religious believers. However, this encounters several obstacles that arise in the form of radicalism, Islamophobia and unpreparedness for dialogue related to religious issues. From these obstacles, various strategies emerged to create tolerance among religious believers, namely the laicite law, integration policies and supporting religious institutions such as the Conseil Francais du Culte Musulman (CFCM). Some of the French government's strategies turned out to be in line with the dimensions of Hifz al-Din which is one of the goals of Maqasid Shari’a. Hifz al-Din in this context, is interpreted repressively then it becomes haq al-tadayyun (religious rights), where this strategy can guarantee the continuity of religious people to worship and carry out religious values. Haq al-Tadayyun not only maintains the sanctity of religion but also creates a harmonious relationship pattern in practicing religion amidst religious diversity. This research has implications for the emergence of a form of tolerance among religious believers in France, therefore, it can be a policy reference for countries with Muslim majority populations in responding to the dynamics that occur due to religious diversity.